2008
DOI: 10.1093/toxsci/kfn207
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles in Zebrafish Brain after Acute Exposure to Domoic Acid at Symptomatic and Asymptomatic Doses

Abstract: Domoic acid (DA) is a neuroexcitatory amino acid that is naturally produced by some marine diatom species of the genus Pseudo-nitzschia. Ingestion of DA-contaminated seafood by humans results in a severe neurotoxic disease known as amnesic shellfish poisoning (ASP). Clinical signs of ASP include seizures and neuronal damage from activation of ionotropic glutamate receptors. However, the impacts of DA exposure at levels below those known to induce outward signs of neurobehavioral exicitotoxicity have not been w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 60 publications
(89 reference statements)
2
44
1
Order By: Relevance
“…Toxicity studies with the zebrafish (Danio rerio) have revealed that exposure to low levels of DA caused different patterns of gene expression than the patterns observed in fish exposed to high doses (Lefebvre et al, 2009). One specific gene, the zebrafish homolog of human N-myc downstreamregulated gene or NDRG4, was markedly downregulated in fish exposed to low levels (Lefebvre et al, 2009). Interestingly, in a separate study, mice that were made NDRG4 protein-deficient had impaired spatial learning and memory in the Morris water maze test (Yamamoto et al, 2011).…”
Section: 3mentioning
confidence: 99%
“…Toxicity studies with the zebrafish (Danio rerio) have revealed that exposure to low levels of DA caused different patterns of gene expression than the patterns observed in fish exposed to high doses (Lefebvre et al, 2009). One specific gene, the zebrafish homolog of human N-myc downstreamregulated gene or NDRG4, was markedly downregulated in fish exposed to low levels (Lefebvre et al, 2009). Interestingly, in a separate study, mice that were made NDRG4 protein-deficient had impaired spatial learning and memory in the Morris water maze test (Yamamoto et al, 2011).…”
Section: 3mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] Although the overt gastrointestinal and neurologic manifestations have defined the disease, emerging evidence from animal and human studies support previously unrecognized threats and novel toxicologic syndromes caused by subclinical toxicity from acute and chronic DA exposures, which may ultimately challenge the adequacy of the current acceptable limit. [15][16][17][18] DA is a potent activator of kainate receptors (KRs) as well as a subpopulation of a-amino-3-hydroxy-5-methyl-4-isoxazoleproprionic acid receptors (AMPARs). 19 The toxic response produced by DA is a coordinated effort, which involves initial activation of KR and AMPAR by DA and secondary activation of N-methyl-D-aspartate receptors (NMDARs) by glutamate, and it is associated with an influx of Ca 2+ across the plasma membrane, inflammation, neuronal cell injury and death, and neurobehavioral alterations.…”
mentioning
confidence: 99%
“…Low DA levels (0.002 to 0.11 Âľg g -1 ) detected in the urine of California sea lions have been associated with a novel neurological syndrome characterized by epilepsy (Goldstein et al 2008). More recently, Lefebvre et al (2009) showed that DA doses below those that cause observable signs of behavioral injury in zebrafish can downregulate several genes involved in important biochemical processes, suggesting potential neurological risk associated with asymptomatic DA exposures. In contrast, experiments with rats have demonstrated that low DA doses can precondition the brain and induce tolerance against higher DA doses in young, but not aged, rats (Kerr et al 2002, Hesp et al 2004.…”
Section: Discussionmentioning
confidence: 99%